Recovery of Mycobacteria from Patients with Cystic Fibrosis - Bange, Franz-Christoph (American Society for Microbiology, 1999)
Despite decontamination, overgrowth by pseudomonads renders cultural isolation of mycobacteria from respiratory specimens of patients with cystic fibrosis (CF) difficult or impossible. We performed a prospective study by comparing levels of reduction of overgrowth and recovery of mycobacteria using either pretreatment with N-acetyl-l-cysteine (NALC)–NaOH alone or pretreatment with NALC-NaOH and then with oxalic acid. From 406 specimens of 148 CF patients, 11 specimens were positive for mycobacteria, 5 of which grew mycobacteria after decontamination by either procedure. Three specimens grew mycobacteria only after decontamination with NALC-NaOH, whereas three specimens grew mycobacteria only after treatment with NALC-NaOH followed by oxalic acid but were overgrown after decontamination with NALC-NaOH. Thus, inactivation of mycobacteria by the more aggressive oxalic acid treatment offsets its beneficial effect of reducing the proportion of cultures overgrown with microorganisms other than mycobacteria.